Enhancing Sustainable Energy Through Cutting-Edge Waste Biorefinery Technologies - Yen-Yi Lee; Masimukku Srinivaas; I-Cheng Li; Kapa Keharika; Ramyakrishna Pothu; Rajender Boddula; Noora Al-Qahtani; Bo-Wun Huang; Guo-Ping Chang-Chien (Reactions)
Biorefineries play a critical role in addressing current global sustainability challenges by converting renewable biomass into valuable products such as biofuels, biochemicals, and bioenergy. The necessity of biorefineries has increased due to the growing demand for eco-friendly alternatives to fossil fuels, mitigating climate change, and reducing environmental impact. Utilizing agricultural byproducts, forest residues, and municipal waste, biorefineries harness feedstock through techniques such as pretreatment, anaerobic digestion, and thermochemical transformation, alongside advanced methods including electrochemical processes, hydrogenation of bio-derived substances, and the implementation of complex biocatalysts within biomass-oriented biorefineries. These processes enhance the efficiency of bioenergy production by breaking down complex biomass into simpler components. The current capacity of biorefineries is expanding globally, with increasing interest in advanced technologies such as gasification, fermentation, and enzymatic conversion. While biorefineries offer significant potential for reducing waste and promoting a circular economy, challenges such as scalability and cost efficiency remain. Future trends include integrating new biotechnological advances and optimizing resource recovery systems to improve yield, profitability, and sustainability in the bioeconomy.